Bahasa Mekongga di Era Digital: Penggunaan Teknologi dalam Pembelajaran di Kolaka - Kadaruddin Kadaruddin; Yusring Sanusi Baso; Gusnawaty Gusnawaty; Munira Hasyim (Journal on Education, 2024)
Mekongga language is a regional language that plays an important role in preserving cultural and historical values ​​for the Kolaka community in Southeast Sulawesi. However, the influence of urbanization and modernization that are developing very rapidly threaten the sustainability of this language. This study aims to provide an overview of the use of technology in learning the Mekongga language in Kolaka and identify appropriate strategies to improve the effectiveness of learning in the digital era. This study uses a qualitative approach, through literature study methods, observations, in-depth interviews, and case studies. The results of the study indicate that the use of language learning technology and e-learning platforms has increased students' motivation in learning the Mekongga language and provided wider access to learning materials, as well as providing creative and innovative learning resources. Collaboration between teachers and technology developers also plays an important role in creating appropriate and useful materials. However, researchers found several obstacles, including technical issues and limited access to technological devices and networks. Ultimately, technology plays a major role in supporting the learning and preservation of the Mekongga language in Kolaka. By using the right strategy and the support of adequate facilities and infrastructure, technology will be an effective medium in maintaining and preserving the Mekongga language in the digital era.